Pengaruh Penggunaan Metode Numbered Head Together (NHT) Terhadap Hasil Belajar Matapelajaran Fiqh Siswa Kelas V Mi Tarbiyatus Shibyan Kembiritan Genteng Banyuwangi - Faizah, Kurniyatul (AL MURABBI, 2023)
This study aims to determine the effect of using the NHT (Numbered Head Together) Method on the learning outcomes of fifth grade students at Madrasah Ibtidaiyah Tarbiyatus Shibyan Kembiritan Genteng Banyuwangi on Fiqh Learning. This type of research is pre experimental designs, which are parts of One Group Pretest - Posttest design. The population in this study were all of the students of fifth grade in Madrasah Ibtidaiyah Tarbiyatus Shibyan which are 25 students. The sample used in this study was all students of fifth grade. The sampling technique is using nonprobability sampling, This research instrument uses multiple choice test items. The collected data is processed using descriptive statistical analysis, normality test, homogeneity test, and hypothesis test. Based on the results the output on the hypothesis test, data shows the results of pretest 70.80 and posttest of 85.64 getting an increase in the amount of 14.24. This is provend by the results of t Test with t count -9,401 and t table 1,711 with sig tailed 0.00 <0.05 with a correlation level of 0.664. So the conclusion is that Ho is rejected and Ha is accepted, which is there is an influence of using the NHT Method on the learning outcomes of fifth grade students at Madrasah Ibtidaiyah Tarbiyatus Shibyan Kembiritan Genteng Banyuwangi on Fiqh Learning.